Novel luminescent chiral network liquid-crystalline polymers containing Sm(iii) ions. Issue 48 (29th April 2016) - Yao, Bing; Cong, Yuehua; Zhang, Baoyan; Wang, Zeqing; Chen, Fei; Sun, Cong
Abstract : Chiral network liquid-crystalline polymers with samarium complexes distributed in spiral matrices can emit soft red light when excited. Abstract : Novel luminescent chiral network liquid-crystalline polymers containing Sm(iii ) ions (Sm-LCPs) exhibiting wonderful liquid crystalline properties and unique fluorescence properties were prepared by poly(methylhydrogeno)siloxane (PMHS), chiral liquid crystal monomer M1, crosslinking agent M2 and samarium complex M3 . The chemical structures, liquid-crystalline behaviours of Sm-LCPs were characterized by various experimental techniques. The introduction of small amount of samarium ions endowed liquid-crystalline polymers with fascinating fluorescence properties. All Sm-LCPs were chiral, and samarium ions did not marked affect the textures of liquid-crystalline polymers. Fourier transform infrared imaging study exhibited that samarium ions were evenly distributed in polymers. A spiral structural model was established to demonstrate the distribution and interaction of components. All Sm-LCPs showed wide mesophase temperature ranges, reversible mesomorphic phase transitions and high thermal stability. The thermogravimetric analysis (TGA) results displayed that the decomposition temperatures (5% weight loss) of all Sm-LCPs were greater than 297 °C. The Sm-LCPs can emit soft red light when excited. Fluorescence intensity of Sm-LCPs gradually increased with increase in samarium complexes from 0.2 to 1.0 mol%. The temperature dependence of luminescence intensity was studied, where the fluorescence intensity of Sm-LCPs decreased monotonically with increase in temperature.